Data representing expert ratings of emotional tone in adjectives used to describe infants and young children - Kaylin E. Hill; Katherine L. Guyon-Harris; Kathryn L. Humphreys (Data in Brief, 2024)
The way caregivers think of their infants and young children may impact caregiving behavior. One way to assess caregivers’ thoughts of their young children is to prompt them to describe the child's personality. Popular methods to analyzing valenced language include the use of software approaches, which have limitations in scoring and application. The present investigation offers an alternative scoring system for the emotional tone of words and phrases relevant to descriptions of infants and children. Using a database of personality descriptions provided by pregnant people and parents to describe their child's personality, we asked experts in infant mental health and related disciplines (N = 51) to rate the words/phrases with regard to the emotional tone or connotation of the descriptive words provided (e.g., positive, neutral, or negative). Experts (i.e., participants) were individuals with self-reported expertise in infants and young children via their profession. Participants were recruited via email to known infant and early childhood mental health practicians and researchers and through participant referral. A total of 496 unique words or phrases were rated by the experts, and in order to reduce participant burden, experts were randomly assigned approximately half of the words. From these ratings, we computed a continuous measure of average valence score across all raters and a categorical variable representing expert consensus (i.e., if ≥80 % of experts agreed it was positive or negative it was assigned that category, otherwise it was assigned neutral). As such, the data provided include caregiver adjectives used to describe their young children, expert ratings of the emotional tone of the provided description, average emotional tone for each word, and expert consensus for each word.